Occurrence of gastrointestinal helminths infection of goats isolated from a farm in Pahang - Mohd Azlan, Mawaddah; Mat Yusof, Afzan; Mohammad, Mardhiah (2016)
Objectives/Research Problem: The aim of this study was to determine and to identify the presence and type of gastrointestinal helminths from the collected fecal sample. Materials and Method: Fecal samples were collected directly from the rectum of 20 goats from a farm located in Kuantan, Pahang. During the collection, the goat’s physical characteristics such as; eye, condition of the body, jaw, and the hair coat, was also observed on each of the goat. Samples were examined within 96 hours for the identification of gastrointestinal helminthic infection by using Formal-ether Sedimentation Method. The identification was done based on the morphology and characteristics of the gastrointestinal helminths and observed under microscope. Results and Discussion: From 20 goats, 18 of it were found to be infected with different species of gastrointestinal helminths. Among the species found are Haemonchus contortus, Triguris spp, Trichostrogylus sp, Ostergia sp. The gastrointestinal helminths species that were identified is varied in each of the samples collected. Conclusion: This study showed that there is presence of gastrointestinal helminths in the collected fecal samples. Hence there is a need for effective system of management, diagnosis and treatment with anthelmintic drugs that can reduce the risk of infection and increase the productivity of the animals.